Primary sensory map formations reflect unique needs and molecular cues specific to each sensory system - Fritzsch, Bernd; Elliott, Karen L; Pavlinkova, Gabriela (F1000Research, 2019)
Interaction with the world around us requires extracting meaningful signals to guide behavior. Each of the six mammalian senses (olfaction, vision, somatosensation, hearing, balance, and taste) has a unique primary map that extracts sense-specific information. Sensory systems in the periphery and their target neurons in the central nervous system develop independently and must develop specific connections for proper sensory processing. In addition, the regulation of sensory map formation is independent of and prior to central target neuronal development in several maps. This review provides an overview of the current level of understanding of primary map formation of the six mammalian senses. Cell cycle exit, combined with incompletely understood molecules and their regulation, provides chemoaffinity-mediated primary maps that are further refined by activity. The interplay between cell cycle exit, molecular guidance, and activity-mediated refinement is the basis of dominance stripes after redundant organ transplantations in the visual and balance system. A more advanced level of understanding of primary map formation could benefit ongoing restoration attempts of impaired senses by guiding proper functional connection formations of restored sensory organs with their central nervous system targets.
Keywords: podněty; čich; primary sensory maps; vestibular map; neurony; Cues; Smell; olfactory map; axony; Animals; cochleotopic map; zvířata; Neurons; taste map; myši; neurogeneze; Axons; retinotopic map; Mice; Neurogenesis